Highly selective cyclohexane oxidation catalyzed by ferrocene in ionic liquid medium - Martins, Luisa (2017)
Background: Although economically very important in view of the significance of the oxidized products for the manufacture of adipic acid and caprolactam (precursors to polyamides widely used in several industries), the current cyclohexane oxidation industrial process leads to very low conversions (ca. 4%) to assure a reasonable selectivity (ca. 85%). Therefore, there is an urgent need to develop sustainable selective cyclohexane oxidation chemistry, which is the main objective of this work. Methods: The partial oxidation of cyclohexane by aqueous tert-butyl hydroperoxide (TBHP, 70% aq. sol.) in phosphonium ionic liquid medium [P6.6.6.14][DCA] and in the presence of catalytic amounts of ferrocene was investigated. The reaction proceeded during 2 h at room temperature. Results: It was found that TBHP, under the above conditions, oxidizeD cyclohexane with high selectivity (> 98%), yielding mainly cyclohexanone (up to 16%, based on the substrate) with total TOFs up to 1 x 104 h-1. Conclusion: The combination of a commercial iron-complex catalyst (ferrocene) and well-adjusted unconventional reaction conditions led to a highly selective, fast and reusable catalytic system for the mild oxidation of cyclohexane. Moreover, the found [Fe(C5H5)2]/[P6.6.6.14][DCA] catalytic system can be of significance to produce polyamide 6.